(untitled) (Journal of Medicine, 2019)
Background: Medical students lead a stressful life and therefore the coping strategy is very important for them to alleviate the stress. The objective of this study was to explore the coping strategy among the first year and third year medical students and also to identify any significant difference between genders and study-years. Materials & methods: This cross-sectional study involved first and third year medical students of University Kebangsaan Malaysia of session 2013/2014. Coping strategy was explored using the ‘Coping Inventory for Stressful Situations’ (CISS) which consist of 48-items where 16 under task-oriented, 16 under emotional-oriented and 16 under avoidance-oriented coping. A five-point Likert’ scale ranging from ‘1=not at all’ to ‘5=very much’ was used to rate the items. Results: Task oriented coping was found the most common strategy among all students while emotion oriented was the least. First year students scored significantly higher than third year showing their best effort to adapt a new environment with insignificant difference between genders. Conclusions: Task-oriented coping strategy of the students is a good sign of problem solving skills. Though majority of the students adapt this method of coping, still there are other methods in practice. Medical school should focus for growing awareness about the positive coping methods in response to stress. This is necessary for the long term benefit of the students as well for better service to the nation. J MEDICINE JUL 2019; 20 (1) : 5-11